A flow-based transition-metal-catalysed hydrogenolysis strategy to facilitate peptide side-chain deprotection. Issue 1 (13th December 2021) - Menti-Platten, Maria; Aldrich-Wright, Janice R.; Gordon, Christopher P.
Abstract : A palladium-catalysed flow chemistry protocol to selectively mediate N β side-chain Cbz-lysis from extended peptide sequences in the presence of trityl, t -butyl and N α -Fmoc protecting groups. Abstract : Orthogonal deprotection methodologies are an invaluable tool for the construction of site-specially modified peptides. Here, we report a facile 10% Pd/CaCO3 -based procedure to selectively mediate Nβ-side-chain Cbz-lysis from extended peptide sequences in the presence of trityl and t -Butyl protecting groups.